Inclusion and Integration of Youth Needs in Youth Empowerment Programmes: Nairobi and Trans Nzoia Counties - Mbugua, Catherine; Kanyinga, Karuti; Mbatia, Paul (European Scientific Journal, ESJ, 2024)
The youth bulge, a rapid population increase of the youth occasioned by reduced infant mortality without a corresponding decrease in fertility among women, has of late become a sore reality in Africa. It has triggered calls for concerted efforts from all development actors in the continent to ensure that youths are engaged in meaningful socio-economic and political advancement of their respective nations. In view of this, a myriad of state and non-state youth empowerment programmes (YEPs) have been developed in Kenya in the last two decades, even as concerns continue being raised on their efficacy and sustainability. The goal of this study was to explore the extent of youth inclusion, and integration of youth needs in YEPs in two counties, Nairobi, an urban setting, and Trans Nzoia, a rural setting. The study adopted a mixed method research approach. First, a comparative survey of the youth was done in Nairobi and Trans Nzoia counties. The cross-sectional survey involved 244 youth respondents in the two counties, and was complemented by Focus Group Discussions (FGDs), key informant interviews and observation. The study established that youths who participate in YEPs are mainly engaged as groups and less often as individuals. In addition, youth inclusion in YEPs is generally wanting, with majority of them in both counties, 53.1% in Nairobi and 59.7% in Trans Nzoia, at least disagreeing that youth decide what programmes to be run in their respective areas. On integration of youth needs, the study found that the youth experience limitations in accessing finance and support from programme officers. The study recommends enhancement of avenues for youth engagement to facilitate efficacy in conceptualization and execution of YEPs in Kenya.